2018
DOI: 10.1136/bmjresp-2018-000331
|View full text |Cite
|
Sign up to set email alerts
|

Baseline clinical characteristics, comorbidities and prescribed medication in a real-world population of patients with idiopathic pulmonary fibrosis: the PROOF registry

Abstract: IntroductionPROOF (a Prospective Observational Registry to Describe the Disease Course and Outcomes of Idiopathic Pulmonary Fibrosis) is an ongoing, observational registry initiated in 2013 with the aim of collecting real-world data from patients with idiopathic pulmonary fibrosis (IPF). Here, we present comprehensive baseline data, which were collected from patients on registry inclusion.MethodsPatients with IPF were enrolled across eight centres in Belgium and Luxembourg. Baseline data collected included dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 35 publications
8
49
0
10
Order By: Relevance
“…Baseline QOL patterns in the IPF-PRO registry were largely consistent with those observed in Insights Pulmonary Fibrosis In Clinical Practice (INSIGHTS-IPF), 24 a multicenter German registry; the Australian IPF Registry (a multicenter cohort of 516 patients) 16 ; and a Prospective Observational Registry to Describe the Disease Course and Outcomes of Idiopathic Pulmonary Fibrosis (PROOF) registry, a cohort of 277 patients enrolled at eight centers in Belgium and Luxembourg. 25 Baseline SGRQ scores in the IPF-PRO registry were nearly identical to baseline SGRQ total scores in the Safety and Efficacy of BIBF 1120 at High Dose in Idiopathic Pulmonary Fibrosis Patients (INPULSIS) trials, 26 despite the longer median time since diagnosis of 1.6 years. Disease severity of patients in the INPULSIS trials (mean CPI, 46.1 27 ; 47.2% GAP Stage I 28 ) was also similar to that of the IPF-PRO registry, which may contribute to the comparable QOL observed.…”
Section: Discussionmentioning
confidence: 84%
“…Baseline QOL patterns in the IPF-PRO registry were largely consistent with those observed in Insights Pulmonary Fibrosis In Clinical Practice (INSIGHTS-IPF), 24 a multicenter German registry; the Australian IPF Registry (a multicenter cohort of 516 patients) 16 ; and a Prospective Observational Registry to Describe the Disease Course and Outcomes of Idiopathic Pulmonary Fibrosis (PROOF) registry, a cohort of 277 patients enrolled at eight centers in Belgium and Luxembourg. 25 Baseline SGRQ scores in the IPF-PRO registry were nearly identical to baseline SGRQ total scores in the Safety and Efficacy of BIBF 1120 at High Dose in Idiopathic Pulmonary Fibrosis Patients (INPULSIS) trials, 26 despite the longer median time since diagnosis of 1.6 years. Disease severity of patients in the INPULSIS trials (mean CPI, 46.1 27 ; 47.2% GAP Stage I 28 ) was also similar to that of the IPF-PRO registry, which may contribute to the comparable QOL observed.…”
Section: Discussionmentioning
confidence: 84%
“…Die Prävalenz nimmt mit steigendem Alter zu [7]. Eine familiäre Häufung der IPF wurde in bis 11 % der Krankheitsfälle beobachtet [9,10].…”
Section: Epidemiologieunclassified
“…Umwelteinflüsse, wie z. B. Exposition gegenüber Asbest, Metall-und Holzstäuben, Chemikalien oder Kontakt mit Allergenen, die üblicherweise bei einer exogen allergischen Alveolitis gefunden werden, konnten in bis zu 38 % der IPF-Patienten eruiert werden, ohne dass ein eindeutiger Kausalzusammenhang hergestellt werden konnte [9,14].…”
Section: Epidemiologieunclassified
See 1 more Smart Citation
“…The two formulations have been shown to be bioequivalent [13], but it is possible that the reduced pill burden associated with the 801 mg formulation may have benefits in terms of adherence and QoL in patients with IPF. Real-world evidence has shown that patients with IPF have a high burden of comorbidities and concomitant medications [16][17][18]; therefore, a simplified pirfenidone dosing regimen may help reduce this burden. An increased number of prescribed daily dose units of medication has been shown to be associated with poorer adherence in patients with a range of conditions [19][20][21], and poor adherence to medications has been found to result in reduced QoL and poorer treatment outcomes [19].…”
Section: Discussionmentioning
confidence: 99%